2013
DOI: 10.1371/journal.pone.0079410
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Combined Application of Ultrasound Imaging Techniques for Middle Cerebral Artery Stent Surveillance and Follow-Up Study

Abstract: ObjectiveIn recent years, cerebral artery stenting has become an effective method for the treatment of cerebral artery stenosis. However, methods for assessing efficacy and techniques for follow-up imaging still need to be developed. This study was designed to evaluate the application of transcranial color-coded sonography (TCCS) in assessing stenting of middle cerebral artery (MCA) stenosis. And, two new imaging techniques (vascular enhancement technology (VET) and 3-dimensional (3D) imaging) were tried out a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…However, as with other endovascular procedures, an effective and convenient method of assessing treatment efficacy and follow-up has not yet been developed. Furthermore, there is insufficient research available to detect the haemodynamic changes that occur following stent placement ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as with other endovascular procedures, an effective and convenient method of assessing treatment efficacy and follow-up has not yet been developed. Furthermore, there is insufficient research available to detect the haemodynamic changes that occur following stent placement ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Digital subtraction angiography (DSA) is the gold standard for diagnosing intracranial arterial stenosis; however, it is expensive, invasive and unable to detect haemodynamic changes. Therefore, DSA cannot be executed within a short time frame and cannot be used for follow-up testing following stent placement ( 10 ). Due to developments in medical imaging technology, various methods exist to study the haemodynamics of these patients, comprising computed tomographic perfusion ( 11 ), positron emission tomography (PET) and single photon emission computed tomography (SPECT) ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few case reports have addressed the application of TCCS in cerebral arterial stenting (Oehm et al 2002;Vicenzini et al 2007). In 2013, the results of a 2-y follow-up on middle cerebral artery stenting were reported by Wang et al (2013). In this study, the immediate relief in stenosis, accompanied by a decrease in flow velocity, indicated that TCCS could be used for assessing treatment efficacy.…”
Section: Discussionmentioning
confidence: 73%
“…Repeated DSA tests within a short span for follow-up after stenting are still limited. Recently, trans-cranial color-coded sonography (TCCS) was reported to be an effective tool for intracranial stenting evaluation (Moreira et al 2012;Wang et al 2013). However, evaluations of the clinical application of TCCS in the management of stenting for IVAS have been lacking.…”
Section: Introductionmentioning
confidence: 99%
“…TCCS has some advantages in diagnosing intra-axial intracranial hematomas (intraparenchymal hematomas), extra-axial intracranial hematomas (epidural and subdural hematomas), brain midline shift, hydrocephaly, brain tumors, cerebral aneurysms, and arteriovenous malformations [21]. Although real-time dynamic morphological information is achieved via color or power Doppler ow imaging of TCCS [23], it has been reported that only 55-80% of basal cerebral arteries can be determined via unenhanced TCCS [24].…”
Section: Introductionmentioning
confidence: 99%